2018
DOI: 10.1186/s12955-018-1022-8
|View full text |Cite
|
Sign up to set email alerts
|

Hip complaints differ across age and sex: a population-based reference data for the Hip disability and Osteoarthritis Outcome Score (HOOS)

Abstract: BackgroundThe Hip disability and Osteoarthritis Outcome Score (HOOS) is a self-administered hip-specific questionnaire intended to evaluate symptoms and functional limitations, and it is commonly used to evaluate interventions in individuals with hip dysfunction or hip osteoarthritis. The HOOS consists of 43 questions in five subscales: Pain, Symptoms, Function in daily living, Function in sport and recreation and Hip-Related Quality of Life. This study aimed to establish population-based reference values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
5
11
1
Order By: Relevance
“…Patients older than 70 years reported more hip-related complaints compared to the younger and there were significant differences in all subscales. This age related difference was in accordance with a study by Sundén et al which was a population based cohort study from Sweden of 840 individuals randomly retrieved, aged 18-84 years [22] . In contrast to our findings, Sundén et al showed that men scored better than women in all subscales regardless of age [22] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patients older than 70 years reported more hip-related complaints compared to the younger and there were significant differences in all subscales. This age related difference was in accordance with a study by Sundén et al which was a population based cohort study from Sweden of 840 individuals randomly retrieved, aged 18-84 years [22] . In contrast to our findings, Sundén et al showed that men scored better than women in all subscales regardless of age [22] .…”
Section: Discussionsupporting
confidence: 92%
“…The hip function in our study was somewhat higher compared to the results in a study of patients with osteoarthritis who underwent a hip arthroplasty and with an average age of 71 [15] . Our results were also equivalent to age and sex matched general population data of Sweden except the domain sport activities that was lower in our study [22] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…But in that study, men scored higher than women in every subscale of HOOS regardless of age which were in contrast to our findings [91]. The results in our study implies that a FNF affects men to a higher degree according to HOOS but the differences were not statistically significant.…”
Section: Study IIIcontrasting
confidence: 99%
“…Younger patients reported less hip-related complains compared to patients above 70 years in every subscale and the differences were statistically significant. Similar findings were demonstrated in a cohort study of normal population in Sweden that included 840 individuals that were randomly included and had an age-span between 18-84 years [91].…”
Section: Study IIIsupporting
confidence: 83%